Numerical coupling strategy using HOS-OpenFOAM-MoorDyn for OC3 Hywind SPAR type platform. (1st November 2022) - Aliyar, Sithik; Ducrozet, Guillaume; Bouscasse, Benjamin; Bonnefoy, Félicien; Sriram, V.; Ferrant, Pierre
Abstract: The coupled (Potential theory and Navier–Stokes) solver is applied to simulate the interaction of sea waves with substructure of floating offshore wind turbines (FOWT) platform, notably similar to the OC3 Hywind SPAR structure. The intention is to develop a numerical tool that allows the study of the survivability of floating structures in extreme sea states. In this study, the moorings are modeled in two ways. One is by considering the mooring lines as a linear spring with defined spring stiffness, and another is by coupling the solver ( foamStar ) with a lumped-mass mooring dynamics model (MoorDyn). MoorDyn represents mooring line behavior subject to axial elasticity, hydrodynamic forces, and vertical contact forces with the seabed. The coupled model has been validated against the experiments carried out as part of the SOFTWIND project. The numerical model results of free surface elevation, floating body motions and mooring tensions are compared with the experiments. For wave cases with mild and moderate amplitudes, mooring in the form of a stiffness matrix is sufficient. However, dynamic mooring simulation (MoorDyn) is required for the extreme sea state conditions. Highlights: Strategic coupling between HOS, OpenFOAM, floating body and mooring is developed Static and dynamic mooring models based on stiffness matrix and MoorDyn, respectively Numerical motions and mooring tensions of SPAR in waves validated with experiments